Determination of median embryo lethal dose for a velogenic Newcastle disease virus isolated in Sulaimani/Iraq - Hiewa Dyary; Rozita Husseiun; Nahla Saeed; Peshnyar Rashid (Basrah Journal of Veterinary Research)
Newcastle disease (ND) is an endemic viral illness in Iraq and has four types: viscerotropic velogenic, neurotropic velogenic, mesogenic, and lentogenic. The virulence of the virus continuously increases, and it is widely spread in wild and domestic birds. Backyard and poultry farm chickens are mainly affected, causing significant economic losses, as the disease is famous for high morbidity and mortality, which may reach 100%. An outbreak of velogenic ND spread in poultry farms in Sulaymaniyah/Iraq in early 2023, causing high mortality rates. Hence, this study was conducted to isolate and identify the virus and determine its median embryo lethal dose (ELD50) in embryonated chicken eggs (ECEs). Samples were taken from chickens suspected of ND, and NDV identification was made by molecular techniques by amplifying part of the 535-base pair-F gene. The virus was passaged three times in ECEs, and the collected allantoic fluid was used to determine the ELD50. After that, fifty ECEs were used to calculate the ELD50. Allantoic fluid dilutions of 10–107 resulted in the death of all embryos after 2-3 days, with distinctive signs of bleeding and hemorrhage. Dilutions of 108, 109, and 1010 resulted in the death of four, two, and one embryo, respectively, and the PCR test revealed NDV infection. The ELD50 was 6.3 ×108 times the allantoic fluid dilution, showing that the virus was very velogenic and necessitated a strict control plan to prevent the disease's further spread.